Magnetic polymer composite membrane as well as preparation method and application thereof

By introducing a magnetic polymer composite film into the friction layer material of the triboelectric nanogenerator, the dielectric constant and surface roughness are improved by RCFO@PDA magnetic nanoparticles, the problem of low charge density of existing friction layer materials is solved, and the current and power output performance of TENG is significantly improved.

CN119775688AActive Publication Date: 2025-04-08JINGCHU UNIV OF TECH

Patent Information

Application Number
CN202510009411.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-08
Estimated Expiration
2045-01-03

Smart Images

  • Figure CN119775688A_ABST
    Figure CN119775688A_ABST
Patent Text Reader

Abstract

The invention provides a magnetic polymer composite film and a preparation method and application thereof, and belongs to the technical field of friction materials. The magnetic polymer composite membrane comprises a P (VDF-TrFE) base membrane and a plurality of rod-shaped CoFe2O4 (RCFO) (at) PDA magnetic nano particles dispersed in the P (VDF-TrFE) base membrane, the RCFO (at) PDA magnetic nanoparticle has a core-shell structure, a core layer is rod-like nanometer CoFe2O4, and a shell layer is polydopamine. The RCFO nanoparticles with dielectric properties are embedded into the P (VDF-TrFE) base film, and a stripe-shaped surface microstructure is successfully constructed through a magnetic field orientation assisted thermal film forming process, so that the contact area of the friction material is effectively increased, and meanwhile, the dielectric constant is also improved. The magnetic polymer composite film provided by the invention is used as a positive electrode friction material of a friction nanometer generator, and the electric output performance of the friction nanometer generator is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of friction materials, and in particular to a magnetic polymer composite film and a preparation method and application thereof. Background Art

[0002] As an emerging energy harvesting technology, the triboelectric nanogenerator (TENG) based on Maxwell displacement current as the driving force is a device that uses friction electrification and electrostatic induction coupling mechanisms to effectively collect low-frequency mechanical energy and convert it into electrical energy. It has the characteristics of simple structure, low cost, strong environmental adaptability, and high output voltage. It can obtain clean and sustainable energy from environmental and biological systems such as mechanical vibration, wind, human movement, and water and convert it into electrical energy.

[0003] A key problem faced by triboelectric nanogenerators during their development is the low surface charge density, which directly affects their current density and power density. The surface charge density is limited by multiple factors, including the electrification charge density of the friction layer material, the charge density during air breakdown, the charge density during friction layer breakdown, and the contact efficiency. The surface roughness of the friction layer material is one of the important factors affecting the performance of triboelectric nanogenerators, because it affects the effective contact area and contact force between the surfaces, thereby affecting the degree of charge separation and current output. In addition to the effective contact area, the improvement of the dielectric properties of the friction layer material has a significant effect on the capacitance of the friction layer material and the ability to store triboelectric charges. At the same time, the increase in the dielectric constant is conducive to the charge density accumulated on the copolymer during physical contact, that is, enhancing the ability of the triboelectric layer to retain surface charges, thereby improving the power output of the triboelectric layer.

[0004] Commonly used friction layer materials include FEP, PVC, PTFE, PVDF and other materials. These materials are selected to improve the triboelectric capacity and surface charge density due to their different electronegativity differences. However, the dielectric constants of these materials are small, which limits the charge density and performance of TENG. Therefore, it is urgent to develop a membrane material with high surface roughness and excellent dielectric properties as a friction layer material to improve the surface charge density of TENG. Summary of the invention

[0005] In view of the technical problems existing in the background technology, the present invention provides a magnetic polymer composite film and a preparation method and application thereof, aiming to solve the technical problem of low surface charge density of TENG caused by low surface roughness and small dielectric constant of existing friction layer materials.

[0006] In the first aspect, the present invention provides a magnetic polymer composite film, including a P(VDF-TrFE) base film and a plurality of RCFO@PDA magnetic nanoparticles dispersed in the P(VDF-TrFE) base film; the RCFO@PDA magnetic nanoparticles have a core-shell structure, the core layer is rod-shaped nano-CoFe2O4, and the shell layer is polydopamine.

[0007] Preferably, the RCFO@PDA magnetic nanoparticles are distributed in a stripe-like manner in the P(VDF-TrFE) based film.

[0008] Preferably, the mass fraction of RCFO@PDA magnetic nanoparticles in the magnetic polymer composite film is 0.5wt%~7wt%.

[0009] Preferably, the mass fraction of RCFO@PDA magnetic nanoparticles in the magnetic polymer composite film is 1 wt %.

[0010] In a second aspect, an embodiment of the present invention provides a method for preparing a magnetic polymer composite film, comprising the following steps: S1. Preparation of rod-shaped nano-CoFe2O4: adding a mixed solution containing a soluble iron salt and a soluble cobalt salt to an oxalic acid solution, mixing well, heating and reacting, filtering, washing, drying and calcining to obtain rod-shaped nano-CoFe2O4; S2. Preparation of RCFO@PDA magnetic nanoparticles: adding the rod-shaped nano-CoFe2O4 to a Tris-HCl buffer solution and mixing evenly, adding dopamine and heating and stirring, filtering, washing, and drying to obtain RCFO@PDA magnetic nanoparticles; S3. Preparation of RCFO@PDA / P(VDF-TrFE) magnetic polymer composite membrane: Disperse the RCFO@PDA magnetic nanoparticles obtained in step S2 in an organic solution of P(VDF-TrFE) to obtain a suspension, dry and solidify the suspension once under the action of an external magnetic field, soak it in water, then remove the external magnetic field and dry and solidify it again to obtain the magnetic polymer composite membrane.

[0011] Preferably, in step S1, the molar ratio of Fe element to Co element in the mixed solution containing soluble iron salt and soluble cobalt salt is 2:1.

[0012] Preferably, in step S1, the soluble iron salt includes at least one of ferric sulfate, ferric nitrate and ferric chloride; and the soluble cobalt salt includes at least one of cobalt sulfate, cobalt nitrate and cobalt chloride.

[0013] Preferably, in step S1, the heating reaction temperature is 180-250° C., and the heating reaction time is 12-24 hours.

[0014] Preferably, in step S1, the calcination temperature is 600-800° C., and the calcination time is 2-4 hours.

[0015] Preferably, in step S2, the pH of the Tris-HCl buffer solution is 8-9.

[0016] Preferably, in step S2, the mass ratio of rod-shaped nano-CoFe2O4 to dopamine is 1:(2-6). The thickness of the outer coating layer can be adjusted according to the content of dopamine.

[0017] Preferably, in step S2, the temperature of heating and stirring is 40-60° C., and the time of heating and stirring is 16-32 hours.

[0018] Preferably, in step S3, the mass concentration of the organic solution of P(VDF-TrFE) is 0.01-1 g / mL.

[0019] Preferably, in step S3, the primary drying temperature is 80-100°C, and the secondary drying temperature is 60-80°C.

[0020] Preferably, in step S3, the film thickness of the magnetic polymer composite film is controlled to be 20-45 μm.

[0021] In some embodiments, in step S3, the suspension is dried and solidified once under the action of an external magnetic field, specifically: the obtained suspension is coated on a substrate to which a magnetic field is applied in a horizontal direction of the substrate, the film thickness is controlled to be 20~45μm, and it is cured in a vacuum drying oven at 80~100°C for 4~8h.

[0022] In some embodiments, in step S3, the external magnetic field is then removed and secondary drying and curing is performed, specifically: the composite film is peeled off from the substrate and dried in a vacuum drying oven at 60-80° C. for 1-2 hours.

[0023] In a third aspect, the present invention provides a friction nanogenerator, wherein the positive electrode friction material of the friction nanogenerator comprises the magnetic polymer composite film provided in the first aspect of the present invention.

[0024] Preferably, the negative electrode friction material of the friction nanogenerator includes a PTFE film.

[0025] The present invention provides a magnetic polymer composite film, which uses rod-shaped nano CoFe2O4 as the main modified material to increase the effective contact area between the filler and the base film P (VDF-TrFE), which helps to promote the charge separation effect during the friction process; the rod-shaped nano CoFe2O4 has a high mechanical stimulation response ability. During the friction process, due to the large shape size and high mechanical strain, the rod-shaped nano CoFe2O4 can more effectively sense the mechanical energy generated by friction and convert it into electrical energy, thereby improving the conversion efficiency.

[0026] The present invention forms RCFO@PDA magnetic nanoparticles with a core-shell structure by polymerizing dopamine with rod-shaped nano CoFe2O4 and dopamine. Due to the self-polymerization of dopamine, a uniform polydopamine (PDA) shell layer can be formed on the surface of the rod-shaped nano CoFe2O4. The coating of the PDA layer can prevent the aggregation of nano CoFe2O4 and improve the uniform dispersion of the particles in the matrix. At the same time, the PDA layer can provide a series of functionalized chemical groups (such as phenolic hydroxyl groups, amino groups, etc.), which can form a strong interaction with the P(VDF-TrFE) matrix and enhance the compatibility of the core-shell structure with the matrix. P(VDF-TrFE) is a commonly used high-performance polymer matrix with good polarization characteristics and can exhibit piezoelectric and ferroelectric properties under an electric field. The presence of the PDA shell layer can improve the dispersion and distribution of RCFO nanoparticles in the P(VDF-TrFE) matrix, so that RCFO can better participate in the polarization process of P(VDF-TrFE), enhance the electrical and magnetoelectric coupling effects of the composite film, and improve its performance in applications such as sensing and energy storage.

[0027] The present invention embeds RCFO@PDA magnetic nanoparticles into the P(VDF-TrFE) base film and successfully constructs a striped surface microstructure through a magnetic field orientation-assisted thermal film forming process, which effectively increases the contact area of ​​the friction material and also improves the dielectric constant. In addition to the effective contact area, the improvement of the dielectric properties of the friction layer material has a significant impact on the capacitance of the friction layer material and the ability to store friction charges. At the same time, the increase in the dielectric constant is conducive to the charge density accumulated on the copolymer during the physical contact process, that is, enhancing the ability of the triboelectric layer to retain surface charges, thereby improving the power output of the triboelectric layer.

[0028] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a magnetic polymer composite film, wherein RCFO@PDA magnetic nanoparticles prepared from rod-shaped nano CoFe2O4 and dopamine are embedded in a P(VDF-TrFE) base film, and a striped surface microstructure is successfully constructed through a magnetic field orientation-assisted thermal film forming process, which effectively increases the contact area of ​​the friction material and also improves the dielectric constant. The magnetic polymer composite film provided by the present invention is used as a positive electrode friction material of a friction nanogenerator, so that the electrical output performance of the friction nanogenerator is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the XRD spectrum of the rod-shaped nano-CoFe2O4 prepared in Example 2 of the present invention; Figure 2 This is a SEM image of rod-shaped nano-CoFe2O4 prepared in Example 2 of the present invention; Figure 3 This is a SEM image of RCFO@PDA magnetic nanoparticles prepared in Example 2 of the present invention; Figure 4 This is a surface morphology SEM spectrum of the RCFO@PDA / P(VDF-TrFE) composite membrane prepared in Example 2 of the present invention; Figure 4 (a) is the SEM spectrum of RCFO@PDA / P(VDF-TrFE) composite membrane at low magnification; Figure 4 (b) is the surface morphology SEM spectrum of RCFO@PDA / P(VDF-TrFE) composite membrane under high magnification; Figure 5 This is an optical microscope image of the RCFO@PDA / P(VDF-TrFE) composite membrane prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0030] The following embodiments of the technical solution of the present invention are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and are therefore only used as examples, and cannot be used to limit the protection scope of the present invention.

[0031] The molar ratio of the monomers VDF:TrFE in the polyvinylidene fluoride-trifluoroethylene P (VDF-TrFE) used in the following examples of the present invention is 70:30.

[0032] 1. Preparation method Example 1 The preparation method of the RCFO@PDA / P(VDF-TrFE) magnetic polymer composite film with a RCFO@PDA content of 0.5wt% comprises the following steps: S1. Preparation of rod-shaped nano-CoFe2O4 (RCFO) First, 8mmol FeSO4·7H2O and 4mmol CoSO4·7H2O were dissolved in a mixed solution of 60mL ethylene glycol and 20mL deionized water, and ultrasonically treated at room temperature for 30min to obtain a mixed solution A. Then, 3mmol oxalic acid (C2H2O4·2H2O) was dissolved in a mixed solution of 60mL ethylene glycol and 20mL deionized water, and magnetically stirred at room temperature for 15min to obtain a mixed solution B. Then, the mixed solution A was added dropwise to the stirred mixed solution B, and stirred for 10min to obtain a mixed solution C. The final mixed solution C was poured into a 200mL PPL-lined autoclave and heated at 200℃ for 12h. After the reaction was completed, the solution was filtered and washed with ethanol and deionized water three times. Then, the dried sample was calcined at 650℃ in a muffle furnace for 2h to obtain rod-shaped nano-CoFe2O4 (RCFO) material.

[0033] S2. Preparation of core-shell structured RCFO@PDA magnetic nanoparticles A 0.1 mol / L Tri-HCl buffer solution was prepared, and the pH value of the solution was controlled at about 8.5. 6 g of dopamine (DA) was weighed and added to the Tri-HCl buffer solution with continuous stirring. After DA was completely dissolved, 1.2 g of RCFO was weighed and added to the prepared solution. The solution was magnetically stirred at 50 °C for 24 h. Under the self-polymerization of dopamine (DA), a polydopamine (PDA) layer was formed on the surface of the rod-shaped nano-CoFe2O4. After the reaction was completed, the solution was filtered, washed with ethanol and deionized water for 3 times, and dried to obtain core-shell structured RCFO@PDA magnetic nanoparticles.

[0034] S3. Preparation of RCFO@PDA / P(VDF-TrFE) magnetic polymer composite film The polyvinylidene fluoride trifluoroethylene P(VDF-TrFE) powder was added to the DMF solvent and stirred continuously for 2 hours to obtain a 0.05g / mL uniform mixed solution. The prepared RCFO@PDA magnetic nanoparticles were mixed with the above uniform solution, and the addition amount of RCFO@PDA magnetic nanoparticles was 0.5wt% of the total mass of P(VDF-TrFE) powder and RCFO@PDA magnetic nanoparticles; and after 1h of ultrasonic treatment, a dispersed suspension was formed. The obtained suspension was coated on a glass substrate with a magnetic field applied in the horizontal direction of the substrate, and the film thickness was controlled to be 30μm. Cured in a vacuum drying oven at 80℃ for 4h, and then, the cured film was soaked in deionized water for 5h. Finally, the composite film was peeled off from the glass substrate and dried in a vacuum drying oven at 60℃ for 1h to obtain a RCFO@PDA / P(VDF-TrFE) composite film with a RCFO@PDA content of 0.5wt%.

[0035] Example 2 The difference between this embodiment and embodiment 1 is that: in step S3, in the preparation of RCFO@PDA / P(VDF-TrFE) composite membrane, the addition amount of RCFO@PDA magnetic nanoparticles is 1wt% of the total mass of P(VDF-TrFE) powder and RCFO@PDA magnetic nanoparticles; the remaining steps are the same as in embodiment 1; and a RCFO@PDA / P(VDF-TrFE) composite membrane with a RCFO@PDA content of 1wt% is obtained.

[0036] Example 3 The difference between this embodiment and embodiment 1 is that: in step S3, in the preparation of RCFO@PDA / P(VDF-TrFE) composite membrane, the addition amount of RCFO@PDA magnetic nanoparticles is 3wt% of the total mass of P(VDF-TrFE) powder and RCFO@PDA magnetic nanoparticles; the remaining steps are the same as in embodiment 1; and a RCFO@PDA / P(VDF-TrFE) composite membrane with a RCFO@PDA content of 3wt% is obtained.

[0037] Example 4 The difference between this embodiment and embodiment 1 is that: in step S3, in the preparation of RCFO@PDA / P(VDF-TrFE) composite membrane, the addition amount of RCFO@PDA magnetic nanoparticles is 5wt% of the total mass of P(VDF-TrFE) powder and RCFO@PDA magnetic nanoparticles; the remaining steps are the same as in embodiment 1; and a RCFO@PDA / P(VDF-TrFE) composite membrane with a RCFO@PDA content of 5wt% is obtained.

[0038] Example 5 The difference between this embodiment and embodiment 1 is that: in step S3, in the preparation of RCFO@PDA / P(VDF-TrFE) composite membrane, the addition amount of RCFO@PDA magnetic nanoparticles is 7wt% of the total mass of P(VDF-TrFE) powder and RCFO@PDA magnetic nanoparticles; the remaining steps are the same as in embodiment 1; and a RCFO@PDA / P(VDF-TrFE) composite membrane with a RCFO@PDA content of 7wt% is obtained.

[0039] Comparative Example 1 The difference between this comparative example and Example 1 is that the addition amount of RCFO@PDA magnetic nanoparticles is 0wt%, and a P(VDF-TrFE) base film is obtained.

[0040] Comparative Example 2 The difference between this comparative example and Example 2 is that the rod-shaped nano-CoFe2O4 material is replaced with commercially available CoFe2O4, and the commercially available CoFe2O4 has a spherical morphology.

[0041] The remaining steps are the same as those in Example 2; a CFO@PDA / P(VDF-TrFE) composite membrane with a CFO@PDA content of 1 wt% is obtained.

[0042] Comparative Example 3 The difference between this comparative example and Example 2 is that step S2 of preparing core-shell structure RCFO@PDA magnetic nanoparticles is omitted, and the rod-shaped nano-CoFe2O4 prepared in step S1 is directly compounded with P(VDF-TrFE), while keeping the CoFe2O4 content the same as that in Example 2.

[0043] Comparative Example 4 The difference between this comparative example and Example 2 is that no magnetic field is applied in step S3.

[0044] Application Example 1 Preparation of triboelectric nanogenerator (TENG): Two 5cm×5cm×0.3cm acrylic plates were prepared as the substrates for the upper and lower electrodes of TENG, and copper foil was pasted on the upper and lower substrates with double-sided tape. Then, the RCFO@PDA / P(VDF-TrFE) composite film with a RCFO@PDA content of 0.5wt% and the PTFE finished film prepared in Example 1 were cut into rectangular blocks of 2cm×2.5cm in size and pasted on the conductive copper foil as the positive and negative friction materials of the device, respectively. The thickness of the positive friction material RCFO@PDA / P(VDF-TrFE) film was 30μm, and the thickness of the negative friction material PTFE film was 0.08 mm.

[0045] Application Example 2 The difference between this application example and application example 1 is that the RCFO@PDA / P(VDF-TrFE) membrane with a RCFO@PDA content of 1 wt% and the PTFE finished membrane prepared in Example 2 are cut into rectangular blocks with a size of 2 cm×2.5 cm and respectively attached to conductive copper foil as the positive and negative electrode friction materials of the device.

[0046] Application Example 3 The difference between this application example and application example 1 is that the RCFO@PDA / P(VDF-TrFE) membrane with a RCFO@PDA content of 3 wt% and the PTFE finished membrane prepared in Example 3 are cut into rectangular blocks with a size of 2 cm×2.5 cm and respectively attached to conductive copper foil as the positive and negative electrode friction materials of the device.

[0047] Application Example 4 The difference between this application example and application example 1 is that the RCFO@PDA / P(VDF-TrFE) membrane with a RCFO@PDA content of 5 wt% and the PTFE finished membrane prepared in Example 4 are cut into rectangular blocks with a size of 2 cm×2.5 cm and respectively attached to conductive copper foil as positive and negative electrode friction materials of the device.

[0048] Application Example 5 The difference between this application example and application example 1 is that the RCFO@PDA / P(VDF-TrFE) membrane with a RCFO@PDA content of 7 wt% and the PTFE finished membrane prepared in Example 5 are cut into rectangular blocks with a size of 2 cm×2.5 cm and respectively attached to conductive copper foil as the positive and negative electrode friction materials of the device.

[0049] Comparative Example 5 The difference between this comparative example and application example 1 is that the P(VDF-TrFE) base film and PTFE finished film prepared in comparative example 1 are cut into rectangular blocks with a size of 2 cm×2.5 cm and respectively attached to conductive copper foil as positive and negative friction materials of the device.

[0050] Comparative Example 6 The difference between this comparative example and application example 1 is that the CFO@PDA / P(VDF-TrFE) composite membrane with a CFO@PDA content of 1 wt% and the PTFE finished membrane prepared in comparative example 2 are cut into rectangular blocks with a size of 2 cm×2.5 cm and respectively attached to conductive copper foil as the positive and negative friction materials of the device.

[0051] Comparative Example 7 The difference between this comparative example and application example 1 is that the composite film and the PTFE finished film prepared in comparative example 3 are cut into rectangular blocks with a size of 2 cm×2.5 cm, which are respectively attached to conductive copper foils as positive and negative friction materials of the device.

[0052] Comparative Example 8 The difference between this comparative example and application example 1 is that the composite film and the PTFE finished film prepared in comparative example 4 are cut into rectangular blocks with a size of 2 cm×2.5 cm, which are respectively attached to conductive copper foils as positive and negative friction materials of the device.

[0053] 2. Test Method 1. Material characterization test (1) Structural characterization of rod-shaped nanocobalt ferrite (RCFO) The rod-shaped nano-cobalt ferrite prepared by the hydrothermal method in step S1 of Example 2 was characterized by an X-ray diffractometer; the morphology of the rod-shaped nano-cobalt ferrite was tested by a scanning electron microscope; and the element surface distribution scanning test of the cobalt ferrite nanorods was performed by an ‌EDX (energy dispersive X-ray spectrometer).

[0054] (2) Characterization of core-shell structured RCFO@PDA magnetic nanoparticles The morphology of the RCFO@PDA magnetic nanoparticles prepared in step S2 of Example 2 was tested using a scanning electron microscope.

[0055] (3) Magnetic properties of RCFO@PDA / P(VDF-TrFE) composite films The hysteresis behavior of the magnetic polymer composite films prepared in Examples 1 to 5 under an external magnetic field as well as their saturation magnetization (Ms) and coercive force (Hc) were tested using a vibrating sample magnetometer (VSM); the test conditions were: 18000 Oe, room temperature.

[0056] (4) Surface morphology characterization of RCFO@PDA / P(VDF-TrFE) composite membrane The morphologies of the different magnetic polymer composite film samples prepared in the examples and comparative examples were characterized by scanning electron microscopy (SEM) and atomic force microscopy (AFM), and the average roughness (Rq) was calculated based on the AFM results.

[0057] (5) Dielectric properties of RCFO@PDA / P(VDF-TrFE) composite films The dielectric properties of the RCFO@PDA / P(VDF-TrFE) composite films oriented in a magnetic field at different RCFO@PDA loadings prepared in the examples and comparative examples were tested by broadband dielectric spectroscopy (Agilent 4284A precision impedance LCR tester); the test conditions were: 10 -2 Hz~10 7 Hz, the temperature range is -60℃~130℃. The dielectric constants of different magnetic polymer composite film samples at 100 Hz ( ɛ r ), dielectric loss and conductivity test results.

[0058] 2. Electrical output performance test of triboelectric nanogenerator (TENG) The two electrodes of the triboelectric nanogenerators prepared in Application Examples 1 to 5 and Comparative Examples 5 to 8 were connected to an electrometer to test the output performance of the TENG. The open circuit voltage (V) of different TENGs was measured during repeated contact and separation cycles at a contact-separation cycle frequency of 5 Hz, a friction layer spacing of 0.1 mm, and a contact force of 15 N. V oc )、Short circuit current( I sc ) and transfer charge ( Q ).

[0059] III. Analysis of test results of various embodiments and comparative examples 1. Structural characterization test results of composite membrane materials (1) Structural and morphological characterization of rod-shaped nano-CoFe2O4 (RCFO) Figure 1 This is the XRD pattern of cobalt ferrite nanorods (RCFO) prepared by hydrothermal method. The diffraction peaks at 30.0°, 35.4°, 43.0°, 53.4°, 56.9°, 62.5° and 74.0° correspond to the (220), (311), (222), (400), (422), (511), (440) and (533) crystal planes of CoFe2O4 (JCPDS No. 22-1086), respectively, indicating that the prepared cobalt ferrite nanoparticles belong to the spinel structure of the cubic system.

[0060] Figure 2This is a high-resolution SEM image of rod-shaped nano-CoFe2O4. The results show that after annealing the CoFe2O4 particles at 650℃ for 2h, a uniform nanorod structure is formed. The high-magnification SEM image clearly shows that the RCFO nanorods are self-assembled from countless nanoparticles with uniform shape and flat surface.

[0061] (2) Morphological characterization of core-shell structured RCFO@PDA magnetic nanoparticles Figure 3 This is the SEM image of RCFO@PDA magnetic nanoparticles. The results show that dopamine forms a uniform polydopamine (PDA) shell on the surface of rod-shaped nano-CoFe2O4 through self-polymerization.

[0062] (3) Magnetic properties of RCFO@PDA / P(VDF-TrFE) composite films Saturation magnetization intensity of different magnetic polymer composite film samples under external magnetic field ( M s) and coercivity ( H c) as shown in Table 1 below.

[0063] Table 1

[0064] The results show that the coercivity of the composite film material remains basically unchanged with the increase of RCFO@PDA content, which is around 1133.3Oe. Under the condition of an external magnetic field of 18000 Oe, the magnetization intensity of the composite film basically reaches saturation; in addition, with the increase of RCFO@PDA doping amount, the Ms of the composite material gradually increases from 0.25 emu / g to 3.6 emu / g, which is mainly due to the increase of RCFO@PDA doping amount, which increases the number of magnetic particles per unit volume of the composite film.

[0065] (4) Surface morphology of RCFO@PDA / P(VDF-TrFE) composite membrane The SEM spectrum of the RCFO@PDA / P(VDF-TrFE) composite membrane prepared in Example 2 is as follows: Figure 4 As shown, Figure 4 (a) is the SEM spectrum of RCFO@PDA / P(VDF-TrFE) composite membrane at low magnification; Figure 4 (b) is a high-magnification SEM spectrum of the surface morphology of the RCFO@PDA / P(VDF-TrFE) composite film. The results show that after the introduction of magnetic dielectric particles RCFO@PDA and the application of a magnetic field, the RCFO@PDA magnetic nanoparticles are distributed in stripes in the P(VDF-TrFE) base film.

[0066] Figure 5This is an optical microscope image of the RCFO@PDA / P(VDF-TrFE) composite film prepared in Example 2 of the present invention. It can be seen that obvious stripes and concave-convex microstructures appear on the surface of the composite film after the RCFO@PDA magnetic nanoparticles are introduced, which increases the effective contact area.

[0067] The average roughness (Rq) was calculated based on the Rq histogram obtained from AFM measurement. The results are shown in Table 2. Table 2

[0068] The results in Table 2 show that the average roughness (Rq) of the pure P(VDF-TrFE) membrane prepared in Comparative Example 1 is 6 nm. Due to the introduction of RCFO@PDA nanoparticles, the roughness of the RCFO@PDA / P(VDF-TrFE) membrane shows a trend of first increasing and then decreasing, especially the RCFO@PDA / P(VDF-TrFE) composite membrane with a RCFO@PDA content of 1wt%, whose Rq increases to 45.8 nm. However, when the RCFO@PDA content exceeds 1wt%, the roughness decreases, indicating that there may be a critical value for the loose arrangement of particles. When the particle content exceeds the critical value, the particles agglomerate, which reduces the roughness of the film compared to the film with loosely arranged particles, but its roughness is still much higher than that of the pure P(VDF-TrFE) membrane. The results of Comparative Example 2 and Example 2 show that the rod-shaped nano-cobalt iron oxide particles are more likely to form irregular structures on the surface of the base film due to their high aspect ratio, thereby increasing the surface roughness; compared with the rod-shaped cobalt iron oxide particles in Example 2, the spherical cobalt iron oxide particles may exhibit lower structural complexity; the high aspect ratio (i.e., length-to-diameter ratio) of the rod-shaped particles makes it easier for them to self-assemble into a structure with obvious bumps on the film surface, increasing the roughness of the film; in contrast, the particles in Comparative Example 2 may have a more symmetrical shape, resulting in a smoother film surface and thus a lower roughness. The results of Comparative Example 3 and Example 2 show that the nano CoFe2O4 particles without dopamine coating are easy to aggregate, resulting in a decrease in the surface roughness of the composite film; dopamine was not used for modification in Comparative Example 3, which means that the surface of the nanoparticles lacks surface modification, and the interaction force between the particles may cause the aggregation of the particles. This aggregation makes the particles form a more uniform and less surface undulation on the surface of the base film, thereby reducing the roughness of the film; in contrast, Example 2 can effectively reduce the aggregation between the particles by PDA coating, maintain the dispersion of the particles, and may cause more surface irregularities, thereby increasing the roughness. The results of Comparative Example 4 and Example 2 show that the surface of the composite film without magnetic field treatment may lack an ordered striped microstructure, resulting in a lower roughness. The magnetic field treatment can guide the magnetic particles to be arranged in a specific direction, thereby forming an ordered surface microstructure and increasing the surface roughness; while the composite film in Comparative Example 4 has not been treated with a magnetic field, resulting in the failure of the magnetic particles to self-assemble into a striped structure on the surface of the base film, and the distribution of the particles may be more random or more uniform, resulting in a smoother surface of the film, thereby lower roughness.

[0069] (5) Dielectric properties of RCFO@PDA / P(VDF-TrFE) composite film Dielectric constants of different magnetic polymer composite film samples at 100 Hz ( ɛ r ) and dielectric loss test results are shown in Table 3 below.

[0070] Table 3

[0071] From the results in Table 3, it can be seen that the dielectric constant of the RCFO@PDA / P(VDF-TrFE) composite film is higher than that of the pure P(VDF-TrFE) film, and the dielectric constant increases with the increase of the RCFO@PDA loading. Since increasing the dielectric constant of triboelectric materials is an effective way to increase the charge density, the increase in the dielectric constant helps to improve the output performance of TENG. The results of Comparative Example 2 and Example 2 show that the high aspect ratio of the rod-shaped magnetic nanoparticles enhances the interface polarization effect, thereby increasing the dielectric constant and dielectric loss; the results of Comparative Example 3 and Example 2 show that the nanoparticles that are not coated with dopamine are prone to agglomeration, increasing the leakage channel, resulting in a significant increase in dielectric loss; the results of Comparative Example 4 and Example 2 show that applying a magnetic field treatment can induce the particles to form an ordered structure, reduce the local electric field distortion, thereby reducing the dielectric loss, and at the same time have a certain optimization effect on the dielectric constant.

[0072] 2. Electrical output performance of RCFO@PDA / P(VDF-TrFE) / / PTFE TENG Under the conditions of contact-separation cycle test frequency of 5 Hz, friction layer spacing of 0.1 mm, and contact force of 15 N, the open circuit voltage ( V oc )、Short circuit current( I sc ) and transfer charge ( Q )The results are shown in Table 4 below.

[0073] Table 4

[0074] The results in Table 4 show that after the introduction of RCFO@PDA particles, the transferred charge increases. Compared with pure P(VDF-TrFE), the electrical output is the highest when the RCFO@PDA / P(VDF-TrFE) composite film with 1wt% RCFO@PDA content is used as the positive friction layer, V oc ,I scThe maximum values ​​of and Q are 5.94 V, 0.102µA, and 1.92nC, respectively. This may be due to the fact that with the increase of RCFO@PDA content, the surface roughness of the composite film gradually increases, and the effective friction area increases during the contact separation process. When the content of magnetic particles is too high, although the dielectric constant increases slightly, the particles are arranged more closely, thereby reducing the roughness of the composite film as a friction layer. Therefore, the corresponding decrease in TENG output performance can be attributed to the combined result of reduced roughness and increased dielectric constant. Because the excessive content of magnetic particles will cause the magnetic particles to be exposed outside the matrix, reducing the effective friction area. The results of Comparative Example 2 and Example 2 show that rod-shaped magnetic particles can more effectively enhance the interface polarization effect and significantly improve the open circuit voltage, short circuit current and transfer charge compared with spherical particles; the results of Comparative Example 3 and Example 2 show that the core-shell structure formed by dopamine coating improves the particle dispersibility and enhances the interface polarization effect, thereby improving the electrical properties of the composite film; the results of Comparative Example 4 and Example 2 show that magnetic field treatment optimizes the interface polarization effect by inducing orderly arrangement of particles, thereby further improving the open circuit voltage, short circuit current and transfer charge performance.

[0075] It should be noted that the present invention is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and embodiments having substantially the same structure as the technical idea and exerting the same effects within the scope of the technical solution of the present invention are all included in the technical scope of the present invention. In addition, within the scope of the main purpose of the present invention, various modifications that can be thought of by those skilled in the art to the embodiments, and other methods of combining some of the constituent elements in the embodiments to construct are also included in the scope of the present invention.

Claims

1. A magnetic polymer composite film, characterized in that: The invention comprises a P(VDF-TrFE) base film and a plurality of RCFO@PDA magnetic nanoparticles dispersed in the P(VDF-TrFE) base film; the RCFO@PDA magnetic nanoparticles have a core-shell structure, the core layer is rod-shaped nano CoFe2O4, and the shell layer is polydopamine.

2. A magnetic polymer composite film according to claim 1, characterized in that: The RCFO@PDA magnetic nanoparticles are distributed in the P(VDF-TrFE) based film in a stripe shape.

3. A magnetic polymer composite film according to claim 1, characterized in that: The mass fraction of RCFO@PDA magnetic nanoparticles in the magnetic polymer composite film is 0.5wt%~7wt%.

4. A method for preparing a magnetic polymer composite film as claimed in any one of claims 1 to 3, characterized in that: The steps include: S1. Preparation of rod-shaped nano-CoFe2O4: adding a mixed solution containing a soluble iron salt and a soluble cobalt salt to an oxalic acid solution, mixing well, heating and reacting, filtering, washing, drying and calcining to obtain rod-shaped nano-CoFe2O4; S2. Preparation of RCFO@PDA magnetic nanoparticles: adding the rod-shaped nano-CoFe2O4 to a Tris-HCl buffer solution and mixing evenly, adding dopamine and heating and stirring, filtering, washing, and drying to obtain RCFO@PDA magnetic nanoparticles; S3. Preparation of RCFO@PDA / P(VDF-TrFE) magnetic polymer composite membrane: Disperse the RCFO@PDA magnetic nanoparticles obtained in step S2 in an organic solution of P(VDF-TrFE) to obtain a suspension, dry and solidify the suspension once under the action of an external magnetic field, soak it in water, then remove the external magnetic field and dry and solidify it again to obtain the magnetic polymer composite membrane.

5. The method for preparing a magnetic polymer composite film according to claim 4, characterized in that: In the step S1, the temperature of the heating reaction is 180-250° C., and the time of the heating reaction is 12-24 hours.

6. The method for preparing a magnetic polymer composite film according to claim 4, characterized in that: In the step S1, the calcination temperature is 600-800° C., and the calcination time is 2-4 hours.

7. The method for preparing a magnetic polymer composite film according to claim 4, characterized in that: In step S2, the pH of the Tris-HCl buffer solution is 8-9; the temperature of the heating and stirring is 40-60° C., and the heating and stirring time is 16-32 hours.

8. The method for preparing a magnetic polymer composite film according to claim 4, characterized in that: The mass ratio of the rod-shaped nano-CoFe2O4 to dopamine is 1:(2-6).

9. The method for preparing a magnetic polymer composite film according to claim 4, characterized in that: In the step S3, the mass concentration of the organic solution of P(VDF-TrFE) is 0.01-1 g / mL; the primary drying temperature is 80-100° C., and the secondary drying temperature is 60-80° C.

10. A friction nanogenerator, characterized in that: The positive electrode friction material of the friction nanogenerator comprises the magnetic polymer composite film described in any one of claims 1 to 3.

Citation Information

Patent Citations

  • Ferromagnet composite polymer nanofilm and preparation method thereof

    CN110372977A

  • Multiferroic composite film and 3D printing preparation method thereof

    CN111925614A

  • Core-shell magnetoelectric composite membrane material as well as preparation method and application thereof

    CN114288466A

  • Preparation method of functional boron nitride modified PVDF (polyvinylidene fluoride)-based nano-composite dielectric film

    JP2023089954A

Cited By

  • Oil stain self-cleaning composite filtering membrane as well as preparation method and application thereof

    CN121927456A